Business Ethics as Field of Teaching, Training and Research in Sub-Saharan Africa - Rossouw, Gedeon Josua (2011)
The article provides an overview of the Sub-Sahara African region and the four sub-regions in which the 44 countries of Sub-Saharan Africa were divided for the purpose of the Sub-Saharan survey of Business Ethics as field of teaching, training and research. A brief overview of existing literature that reflects on training, teaching and research in the field of Business Ethics in the Sub-Sahara African region is given, after which the research process and methods that were used in the survey are introduced. Then a comparative summary of the findings across the four sub-regions (Western Africa, Southern Africa, Eastern Africa and Francophone Africa) in the region is presented. The discussion of the findings commences with a discussion on the terminology that is used to refer to Business and Economic Ethics in Sub-Saharan Africa. It then provides an overview of the prevalence and distribution of Business Ethics as field of teaching, training and research in Sub-Saharan Africa that demonstrates the substantial growth in the field of Business Ethics since 2000 when an earlier survey was conducted. The focus areas in the field of Business Ethics are identified as well as the major themes that were found with regard to teaching, training and research in Business Ethics. Also the major challenges that are foreseen in the field of Business Ethics over the next 5 year are discussed. Finally, a number of concluding remarks are made that highlight unique features and challenges in the current state of Business Ethics in Sub-Saharan Africa.
Keywords: Economic Ethics; Business Ethics; Survey; Sub-Saharan Africa; Research; Training; Teaching